Conocimientos sobre diagnóstico y prevención del cancer oral en estudiantes de la clínica integral de la Facultad de odontología UAN (2023)
Introduction. Oral cancer is a pathology of great importance in public health, because it is one of the diseases of the oral cavity that threatens the life of the individual. Approximately 300,000 new cases of oral cancer are diagnosed annually in the world, of which 75% are found in developing countries, generally in advanced stages. On the other hand, in Colombia the information related to the risk of suffering from oral cancer is quite limited. O